2019
DOI: 10.1101/620799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Escherichia coli Transcriptome Mostly Consists of Independently Regulated Modules

Abstract: Underlying cellular responses is a transcriptional regulatory network (TRN) that modulates gene expression. A useful description of the TRN would decompose the transcriptome into targeted effects of individual transcriptional regulators. Here, we applied unsupervised learning to a compendium of high-quality Escherichia coli RNA-seq datasets to identify 70 statistically independent signals that modulate the expression of specific gene sets. We show that 50 of these transcriptomic signals represent the effects o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 71 publications
1
52
0
Order By: Relevance
“…However, beyond regulons, i-modulons can also describe other genomic features, such as strain differences and genetic alterations (e.g. gene knock-out) that can lead to change in gene co-expression 9,11 . The outcome of this approach is a biologically relevant, low dimensional mathematical representation of functional modules in the TRN that reconstruct most of the information content of the input RNAseq compendium ( Figure S1b ).…”
Section: Ica Extracts Biologically Meaningful Components From Transcrmentioning
confidence: 99%
“…However, beyond regulons, i-modulons can also describe other genomic features, such as strain differences and genetic alterations (e.g. gene knock-out) that can lead to change in gene co-expression 9,11 . The outcome of this approach is a biologically relevant, low dimensional mathematical representation of functional modules in the TRN that reconstruct most of the information content of the input RNAseq compendium ( Figure S1b ).…”
Section: Ica Extracts Biologically Meaningful Components From Transcrmentioning
confidence: 99%
“…To make sense of these expression changes, we applied an alternative RNA-seq analysis workflow that was shown to enable quantitative analysis of the E. coli transcriptome from the perspective of transcription factors (Sastry et al , 2019b) . The authors showed that independent component analysis (ICA) deconvolved a large compendium of E. coli MG1655 RNA-seq data into a linear combination of independent sources that reflect known regulons ("iModulons"), and source weightings ("iModulon activities"), which describe the global regulatory state (Sastry et al , 2019a) . Using the previous set of 92 iModulons, we transformed the flask-specific gene expression profiles into flask-specific iModulon activities (see Methods, Supplementary Figure 2 ).…”
Section: Characteristics Of Transcriptome Adaptation In E Colimentioning
confidence: 99%
“…Transcription factor and GO enrichments of differentially expressed gene sets Transcription factors (TFs) and the genes they are known to regulate were obtained from a study (Fang et al , 2017) . GO terms were obtained from (Sastry et al , 2019a) . This list was used to perform hypergeometric enrichment analysis of the differentially expressed genes determined from RNAseq analysis.…”
Section: Differential Expression Analysis Of Rna-seqmentioning
confidence: 99%
“…Here, however, we consider the mutations on rpoC to be associated with inducing faster growth rather than acid resistance. A comprehensive analysis on the 278 gene expression datasets of E. coli across diverse conditions has revealed that mutations on genes related to RNA polymerase typically lead to improved growth rate and reduced stress-related gene expression [41].…”
Section: Discussionmentioning
confidence: 99%
“…The study here provides a novel perspective on acid resistance mechanisms, as the commonly known acid resistance systems depend on rich medium or specific amino acids [42,43]. In addition to the analysis of genetic mutations and DEGs, further analysis can be performed to understand the change in regulatory actions using a recently developed approach [41]. Such analysis can be helpful in understanding the response to acid stress at the level of transcriptional regulation and revealing potential drivers behind the global adjustment of cellular response against acid stress.…”
Section: Discussionmentioning
confidence: 99%